Enhanced Efficacy of Chemically Modified Curcumin in Experimental Periodontitis: Systemic Implications [Corrigendum] - Wang HH; Lee HM; Raja V; Hou W; Iacono VJ; Scaduto J; Johnson F; Golub LM; Gu Y (Dove Medical Press, 2020)
Wang HH, Lee HM, Raja V, et al. J Exp Pharmacol. 2019;11:1–14.On page 13 the disclosure section should be presented as follows:DisclosureLMG is listed as an inventor on several related patents and these have been fully assigned to his institution, Stony Brook University, The State University of New York (SUNY). FJ is also listed as an inventor on several related patents which have been fully assigned to Stony Brook University and to Chem-Master Int. Inc. on a shared basis. In addition, both LMG and FJ are minor shareholders in Traverse BioSciences, Inc., and JS is president and major shareholder in Traverse. All other authors declare that there are no conflicts of interest regarding the publication of this paper.Read the original article